2004
DOI: 10.1093/hmg/ddh261
|View full text |Cite
|
Sign up to set email alerts
|

Reduced hepatic expression of farnesoid X receptor in hereditary cholestasis associated to mutation in ATP8B1

Abstract: Farnesoid X receptor (FXR) is a transcription factor that controls bile acid homeostasis. The phenotype of Fxr null mice is characterized by hypercholanaemia, impaired secretion of bile acids and failure to thrive. Human disorders with these characteristics include FIC1 disease (caused by mutations in ATP8B1, which encodes a putative aminophospholipid translocase, FIC1, whose function in bile handling is unknown) and bile salt export pump (BSEP) disease (caused by mutation in ABCB11, which encodes BSEP, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 56 publications
4
66
1
Order By: Relevance
“…Previous studies have outlined putative functions of ATP8B1 in hepatocytes and in enterocytes. 5,13,14 In the present study, we provide evidence that cholangiocytes are a site of high endogenous expression of ATP8B1 in the liver and biliary tract. Furthermore, the ATP8B1 defect was associated with a downregulation in the expression of CFTR, a key player in the physiology of these cells.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Previous studies have outlined putative functions of ATP8B1 in hepatocytes and in enterocytes. 5,13,14 In the present study, we provide evidence that cholangiocytes are a site of high endogenous expression of ATP8B1 in the liver and biliary tract. Furthermore, the ATP8B1 defect was associated with a downregulation in the expression of CFTR, a key player in the physiology of these cells.…”
Section: Discussionsupporting
confidence: 55%
“…8,27 Recently, two groups reported on decreased FXR mRNA levels in the liver and intestine of patients with PFIC1, with subsequent downregulation of BSEP mRNA in the liver, and upregulation of ASBT mRNA in the intestine. 13,14 Both groups have suggested that impaired ATP8B1 function resulted in reduced FXR expression and/or activity with subsequent impairment of canalicular and ileal bile salt transport, which would be causative for the cholestatic phenotype. Yet, in the present study, patients with PFIC1 as well as patients with other types of cholestatic diseases (PFIC2 and biliary atresia) showed reduced hepatic expression of FXR, suggesting that the drop in FXR levels is secondary to cholestasis.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,12,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][57][58][59] This study showed that some ABCB11 missense mutations were associated with splicing defects, most caused protein processing defects, and the two functionally analyzed showed a reduction in taurocholate transport. Additionally, the ability to modulate splicing and protein processing defects was examined; some mutations were amenable to such treatments.…”
Section: Discussionmentioning
confidence: 76%
“…It plays an integral role in phospholipid translocation. Proposed mechanisms for cholestasis include reduced bile salt secretion due to farnesoid X receptor (FXR) downregulation and overloading of bile acids in hepatocytes due to bile salt export pump (BSEP) downregulation and increased bile acid synthesis within hepatocytes [61,62]. High expression of the ATP8B1 gene is also noted in the cholangiocytes, small bowel, kidney and pancreas and may account for the symptoms of diarrhoea and pancreatic insufficiency in PFIC1 patients.…”
Section: Genetic Cholestatic Disordersmentioning
confidence: 99%